Beyond Criminal Approach: A Critical Analysis of Civil-Based Asset Recovery System as an Alternative Solution for Corruption Cases in Indonesia - Fauzan Akbar; Ahmad Ibrahim Badry (Faculty of Law, Universitas Pekalongan, 2025)
This research examines the effectiveness of the civil approach in returning assets resulting from corruption offences as an alternative to the conventional criminal approach in Indonesia. Although efforts to eradicate corruption have been intensively carried out through criminal channels, the level of return of state assets is still not optimal. Using a normative juridical research method with conceptual and comparative approaches, this research analyses the potential of a civil-based asset recovery system in overcoming the limitations of the criminal approach. The results show that the civil approach has several strategic advantages, including a lower standard of proof and a focus on asset recovery compared to the criminal approach. lower standard of proof and a focus on asset recovery compared to the punishment of the perpetrator. However, its implementation still faces considerable challenges related to inter-agency coordination and the limited capacity of law enforcement officials. law enforcement officials. It is necessary to strengthen corruption eradication strategies through synergy between law enforcement agencies. This research recommends policy reformulation that integrates the civil approach into the national anti-corruption system as a complement to the national system as a complement to the existing criminal mechanism. The contribution of this research is to present a comprehensive analysis of the urgency and modalities of implementing a civil-based asset recovery system in the context of corruption eradication in Indonesia.